Conflict fuels inflation but the tinder lies elsewhere: Eclectic structuralist thoughts in a developing economy context - Arslan Razmi (University of Massachusetts, Department of Economics, 2023)
Developing country inflation is in the headlines again. Mainstream macroeconomics typically ignores the role of conflict while non-mainstream work tends to ignore macroeconomic constraints. This paper revisits the issue employing a dependent economy framework with eclectic characteristics. Specifically, I explore the mechanisms that propagate both real and monetary sources of inflation in the presence of real wage resistance and distributional conflict. The analysis shows that the inability to pay for subsidies with taxes or bond issuance in a stylized developing economy could create a situation where a relatively small shock leads to sustained and accelerating inflation and a wage-price spiral, thanks to conflicting claims on income. Subsidies to protect consumers from external price shocks could, similarly, leave a country vulnerable to accelerating wage-price spirals as the relative price effects of a declining foreign asset position are dampened. Distributional conflict thus plays the role of sustainer rather than the primum mobile. Price controls could, in theory, better enable inflation management if these do not result in redistribution towards spenders. Such controls, however, create other trade-off for countries facing balance-of-payments fragility.
Keywords: E31; O23; E64; F41; 330; Budget deficits; seigniorage; distributional conflict; consumption subsidies; price controls; structuralist macroeconomics